PENERAPAN PEMBELAJARAN MENGGUNAKAN MEDIA BERBASIS IT (INFORMATION TEACHNOLOGI)KELAS VI DI SD N 27 LADANG HUTAN - Rika Sri Wahyuni; M. Isnando Tamrin; Nelfanita (CV. ADIBA AISHA AMIRA, 2023)
This article is the result of research which aims to determine the application of information technology- based learning in order to support teacher performance, and what are the obstacles and strategies for implementing information technology-based learning. This research uses a type of qualitative research with a naturalistic approach with primary data sources namely the principal, class teachers and students, while secondary data comes from various documents and writings. Data collection used observation techniques, in-depth interviews and several documentation attachments. Data analysis techniques start from data reduction, presenting data and drawing conclusions. The results of the research show that the application of learning using information technology-based media can support teacher performance and students can be active and focused in capturing the learning provided by the teacher. Where by using information technology-based media the process of delivering material is easier and varied in the learning material that will be taught. There are still several obstacles and efforts experienced by teachers and students who have not yet mastered information technology, but these can be overcome. The most popular learning media nowadays is IT-based learning media. IT-based learning media is audio-visual media. With this audio visual, it can grow and even increase the learning motivation of students at all levels of education. IT- based learning media can be electronic, for example; web ebooks, e-modules, flash, interactive multimedia CDs and so on.